Microglia-Derived Microvesicles Affect Microglia Phenotype in Glioma - Grimaldi, Alfonso; Serpe, Carmela; Chece, Giuseppina; Nigro, Valentina; Sarra, Angelo; Ruzicka, Barbara; Relucenti, Michela; Familiari, Giuseppe; Ruocco, Giancarlo; Pascucci, Giuseppe Rubens; Guerrieri, Francesca; Limatola, Cristina; et al. (Frontiers in Cellular Neuroscience, 2019)
Extracellular-released vesicles (EVs), such as microvesicles (MV) and exosomes (Exo) provide a new type of inter-cellular communication, directly transferring a ready to use box of information, consisting of proteins, lipids and nucleic acids. In the nervous system, EVs participate to neuron-glial cross-talk, a bidirectional communication important to preserve brain homeostasis and, when dysfunctional, involved in several CNS diseases. We investigated whether microglia-derived EVs could be used to transfer a protective phenotype to dysfunctional microglia in the context of a brain tumor. When MV, isolated from microglia stimulated with LPS/IFN were brain injected in glioma-bearing mice, we observed a phenotype switch of tumor associated myeloid cells (TAMs) and a reduction of tumor size. Our findings indicate that the MV cargo, which contains upregulated transcripts for several inflammation-related genes, can transfer information in the brain of glioma bearing mice modifying microglial gene expression, reducing neuronal death and glioma invasion, thus promoting the recovery of brain homeostasis.